Is atrial fibrillation associated with poor outcome after thrombolysis? - Sanák, Daniel; Herzig, Roman; Král, Michal; Bártková, Andrea; Zapletalová, Jana; Hutyra, Martin; Skoloudík, David; Vlachová, Ivanka; Veverka, Tomás; Horák, David; Kanovský, Petr (Journal of neurology, 2010)
Atrial fibrillation (AF) is considered a predictor for severe stroke and poor outcome. The aim was to evaluate whether AF is associated with poor outcome in acute ischemic stroke (IS) patients treated with intravenous thrombolysis (IVT). In a retrospective study, 157 consecutive IS patients (98 males, mean age 67.3 +/- 10.2 years), treated with IVT within 3 hours from stroke onset, were divided into two groups according to presence/absence of AF. Neurological deficit was evaluated using the NIHSS on admission, 24 hours, and 7 days later, while the 90-day clinical outcome was assessed using the modified Rankin Scale (mRS). A total of 66 patients (38 males) presented with AF. The baseline NIHSS was 13.3 +/- 5.4 in AF and 11.0 +/- 5.1 points in non-AF patients (P = 0.006). AF patients had arterial occlusions more frequently in the baseline MRA (54.5% in AF versus 25.3% in non-AF, P = 0.0002). No differences were found between groups in clinical improvement after 24 hours and 7 days or in rate of achieved recanalizations. AF patients had significantly poorer 90-day clinical outcome than non-AF patients (median mRS 2.5 vs. 1.0). Patients with AF had significantly worse 90-day clinical outcome after IVT compared to those without AF, probably due to more severe baseline neurological deficits and the greater number of arterial occlusions in the MRA before IVT.
Keywords: trombolytická terapie; výsledek terapie; Male; retrospektivní studie; Middle Aged; prognóza; cévní mozková příhoda; Adult; Stroke; Aged; dospělí; mužské pohlaví; senioři; ischemie mozku; Severity of Illness Index; Thrombolytic Therapy; Atrial Fibrillation; Treatment Outcome; Time Factors; akutní nemoc; Acute Disease; senioři nad 80 let; lidé; ženské pohlaví; Humans; časové faktory; Aged, 80 and over; Prognosis; stupeň závažnosti nemoci; Retrospective Studies; Female; lidé středního věku; fibrilace síní; Brain Ischemia